Perancangan Time Synchronization Sebagai Alat Bantu Pengujian Intertrip Relay Distance - Ryan Wicaksono; R Jasa Kusumo Haryo; Apriando Ravi Dwi Santoso; Endrik Dwi Wibowo; Pembri Ridho Hanafi (Universitas Darul Ulum, 2024)
At the company PT. PLN (Persero) ULTG Madiun carried out many tests relay, one of which is intertrip testing relay distance. Intertrip testing relay distance is a test carried out between 2 (two) relay distance conducting bays in main substations that face each other. Intertrip testing relay distance must be done if replacement occursrelay, replacement of teleprotection equipment, changes to protection schemes, and changes to logic circuitsrelay which is related to the send or receive signal from the opposite substation. However, this test requires synchronization between two intertrip test tools relay distance at each substation. In this final project, it will be designed Time Syncronization As A Tool For Intertrip Relay Distance Testing, to make things easier for PT employees. PLN (Persero) ULTG Madiun when synchronizing two intertrip test equipment relay distance. All process control of this tool uses ESP32 Devkit V1. Meanwhile for displaying setting time for testing can be seen on the web assisted by GPS NEO-6M. The results obtained when testing the Dolopo by Ponorogo R and S phase distance intertrip relay were carried out at 12.00.00, experiencing a delay time of 0.0553 seconds when the PMT tripped. Meanwhile, the Dolopo by Ponorogo T phase distance intertrip relay test was carried out on 12.09.00 and experienced a delay of 0.0529 seconds when the PMT tripped. From two intertrip relay distance tests, the trip time delay is no more than 0.1 second.